2019
DOI: 10.1007/s11307-019-01455-x
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Imaging with Second-Window Indocyanine Green in Newly Diagnosed High-Grade Gliomas Predicts Gadolinium Enhancement on Postoperative Magnetic Resonance Imaging

Abstract: Purpose: Intraoperative molecular imaging with tumor-targeting fluorophores offers real-time detection of neoplastic tissue. The second window indocyanine green (SWIG) technique relies on passive accumulation of indocyanine green (ICG), a near-infrared fluorophore, in neoplastic tissues. In this study, we explore the ability of SWIG to detect neoplastic tissue and to predict postoperative magnetic resonance imaging (MRI) findings intraoperatively. Procedures: Retrospective data were collected from 36 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 44 publications
(55 reference statements)
0
21
0
Order By: Relevance
“…Other studies have demonstrated ICG's ability to visualize chordoma, craniopharyngioma, pineocytoma, and intraventricular tumors. 16,22,23 Because the ultimate goal of FGS is to maximize extent of resection, studies by Cho et al in 2020 24 and Teng et al 76 comparing NIR fluorescence to the gold standard postoperative MRI showed that the absence of re- sidual NIR signal postresection closely correlated to GTR of HGGs (p < 0.0001) and intracranial metastases (p = 0.007) on MRI. One limitation of these findings, however, is intrinsic to the SWIG technique itself.…”
Section: Clinical Trials Of Icg For Fluorescence-guided Intracranial mentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have demonstrated ICG's ability to visualize chordoma, craniopharyngioma, pineocytoma, and intraventricular tumors. 16,22,23 Because the ultimate goal of FGS is to maximize extent of resection, studies by Cho et al in 2020 24 and Teng et al 76 comparing NIR fluorescence to the gold standard postoperative MRI showed that the absence of re- sidual NIR signal postresection closely correlated to GTR of HGGs (p < 0.0001) and intracranial metastases (p = 0.007) on MRI. One limitation of these findings, however, is intrinsic to the SWIG technique itself.…”
Section: Clinical Trials Of Icg For Fluorescence-guided Intracranial mentioning
confidence: 99%
“…25 mg ICG video angiography in 54 HGGs, 17 LGGs, 14 meningiomas, 12 metastases, & 3 hemangioblastomas can monitor blood flow in exposed tumoral & peritumoral vessels Zeh et al, 2017 9 HGG Mean SBR of 7.5 w/ 2.5-5.0 mg/kg SWIG in 10 pts, plateau of ICG NIRF up to 48 hrs postinfusion Cho et al, 2020 24 Newly diagnosed HGG showing weak or no protoporphyrin-IX fluorescence but strong SWIG fluorescence. 29 Another comparison study demonstrated that ICG was superior to 5-ALA in visualizing areas of increased angiogenesis, a process essential for metastasis of solid tumors.…”
Section: Gliomamentioning
confidence: 99%
“…Our experience with the new operating microscope in Blue400 and Yellow560 modes demonstrates that the two channels can be alternated without compromising image quality. Concurrent FNa-contrasted CLE may be advantageous during surgeries performed using near-infrared guidance (e.g., using indocyanine green [ICG]) because of the absence of spectral overlap with FNa (24,25). Confocal-assisted fluorescence microscopy with ICG as a contrast has also been reported (26,27).…”
Section: Implications For Practice: Incorporation Of Cle Into the Wormentioning
confidence: 99%
“…Zeh et al administered doses above the FDA-approved limit of 2 mg/kg in rodents implanted with human glioma xenografts and demonstrated a broad plateau period extending up to 72 h, thus allowing for optimal imaging of glioma as compared to normal brain ( 20 ). With the SWIG approach, combining the natural permeability of the tumor vascularity with poor clearance allows for high doses of ICG to penetrate the tumor, a high dose (5 mg/kg) of intravenous ICG is given a day (24 h) prior to surgery, yielding improved intraoperative visualization of the tumor compared to white light ( 15 , 27 , 28 ). In a series of 15 gliomas featuring 11 HGG, sensitivity was 98% and specificity 45% ( 27 ).…”
Section: Indocyanine Green (Icg)mentioning
confidence: 99%